1. Identify the coordinates of the first point: (-2, 1)
2. Identify the coordinates of the second point: (4, 3)
3. Use the distance formula:
Distance = √((x2 - x1)² + (y2 - y1)²)
4. Substitute the coordinates into the formula:
Distance = √((4 - (-2))² + (3 - 1)²)
Distance = √((4 + 2)² + (3 - 1)²)
Distance = √(6² + 2²)
Distance = √(36 + 4)
Distance = √40
5. Simplify the square root:
Distance ≈ 6.32
6. The distance between the two points is approximately 6.32.
Put the steps in order to find the distance between these 2 points.
(-2, 1)
(4, 3)
(7 points)
1 answer